Comparation Test on High-Quality Flax Resources for Oil and Fiber Production in Kazakhstan - Caisheng Qiu; Aliya Baitelenova; HuaJiao Qiu; Gani Stybayev; Dingxiang Peng; Jianhua Chen; Gulden Kipshakbayeva; Yufu Wang; Almagul Begalina; Zhimin Wu (Journal of Natural Fibers, 2023)
Oil flax stems are often burnt because of the low fiber content; this issue is especially serious in Kazakhstan. To solve this problem, this study aimed to determine which flax resources could exhibit a significant increase in stem yield without a decrease in seed yield. In a previous study in 2019, we tested seven types of flax stems at the research site of the S. Seifullin KATU campus. Here, a further investigation of the same resources, which was conducted in 2020, is described. According to the results, the UF03, UF05, and UF06 showed higher dynamics of plant height in the budding and blooming stages compared to a local Kazakhstani variety; this result greatly differed compared with the data from 2019. UF03 yielded the best oil quality, especially in terms of the linolenic acid and linoleic acid contents. UF02 had good performance in terms of yield and the largest fat content of all resources. More foreign flax resources should be introduced to improve the development of the flax industry in Kazakhstan.